2016
DOI: 10.1177/0300985816658102
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Lung Lesions in Aging Laboratory Rabbits (Oryctolagus cuniculus)

Abstract: Spontaneous age-related lesions of laboratory rabbits are not well documented in the contemporary scientific literature. A retrospective study of diagnostic necropsies of 36 rabbits >2 years of age found a number of common lung lesions. Fibromuscular intimal hyperplasia affected medium and to a lesser extent large pulmonary arteries and was present to a variable extent in all 36 rabbits >2 years of age. The lesions were characterized by fragmentation and/or reduplication of the internal elastic lamina (IEL), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…7,23,27,83 Additionally, small fibropapillomas have been described in a population of rabbits, all of which were older than 2 years, with a mean age of 4 years, and without Shope papilloma virus exposure. 20 Lesions were characterized by epithelial papilliform proliferation with a prominent fibrous stalk.…”
Section: Respiratory Systemmentioning
confidence: 99%
“…7,23,27,83 Additionally, small fibropapillomas have been described in a population of rabbits, all of which were older than 2 years, with a mean age of 4 years, and without Shope papilloma virus exposure. 20 Lesions were characterized by epithelial papilliform proliferation with a prominent fibrous stalk.…”
Section: Respiratory Systemmentioning
confidence: 99%
“…Early foam cell accumulation to partly occlusive atheromatous plaques were observed in the larger lung arteries 28 . Unique proliferations are seen as age related changes in the pulmonary arteries of both sexes and can resemble iatrogenic lesions 177 . Genetically altered strains of the NZW rabbit such as the Watanabe rabbit (Watanabe heritable hyperlipidemia rabbit, WHHL) are also used extensively.…”
Section: Section 13: Respiratory Systemmentioning
confidence: 99%
“…Comments: Cooper et al reported a congenital surfactant pneumonia in the audiogenic (EIII/JC) strain of rabbits 177 . This pneumonia was frequently grossly visible as irregular firm tan nodules in the cranioventral portions of lung lobes.…”
Section: Section 13: Respiratory Systemmentioning
confidence: 99%
“…The next most popular choice, fibropapilloma (13%), was also not a preferred diagnosis of the INHAND rabbit coauthors. While similar lesions have been described as fibropapillomas in the lungs of aging rabbits (Cooper et al 2017), the rabbit INHAND coauthors do not see evidence that this is a neoplastic process. During the open discussion at the end of the talk, there was general agreement that this was a common, nonspecific response to pulmonary injury and should not be labeled as a neoplasm.…”
Section: Select Cases From the Rabbit Inhand Working Groupmentioning
confidence: 94%